In defense of quantitative metrics in researcher assessments. - John P A Ioannidis; Zacharias Maniadis (PLoS Biology, 2023)
Qualitative assessments of researchers are resource-intensive, untenable in nonmeritocratic settings, and error-prone. Although often derided, quantitative metrics could help improve research practices if they are rigorous, field-adjusted, and centralized.